2006
DOI: 10.1002/ajpa.20477
|View full text |Cite
|
Sign up to set email alerts
|

Do food availability, parasitism, and stress have synergistic effects on red colobus populations living in forest fragments?

Abstract: Identifying factors that influence animal density is a fundamental goal in ecology that has taken on new importance with the need to develop informed management plans. This is particularly the case for primates as the tropical forest that supports many species is being rapidly converted. We use a system of forest fragments adjacent to Kibale National Park, Uganda, to examine if food availability and parasite infections have synergistic affects on red colobus (Piliocolobus tephrosceles) abundance. Given that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
180
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 228 publications
(185 citation statements)
references
References 63 publications
0
180
2
3
Order By: Relevance
“…Chapman et al (15) recently showed that red colobus in forest fragments near Kibale suffer increased gastrointestinal parasitism with helminths as a result of nutritional stress and that this effect has led to a decline in population. Gillespie and Chapman (12) documented that the degree of disturbance of a fragment (measured as the density of tree stumps) was an accurate predictor of prevalence of infection of red colobus with parasitic nematodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chapman et al (15) recently showed that red colobus in forest fragments near Kibale suffer increased gastrointestinal parasitism with helminths as a result of nutritional stress and that this effect has led to a decline in population. Gillespie and Chapman (12) documented that the degree of disturbance of a fragment (measured as the density of tree stumps) was an accurate predictor of prevalence of infection of red colobus with parasitic nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Fragmentation also alters patterns of gastrointestinal helminthic and protozoan infection in certain species (12)(13)(14). Whether host susceptibility, transmission dynamics, or a combination of these factors drive such trends remains unclear (15). The effects of fragmentation on the dynamics of pathogen transmission between primates and other species, including humans, are largely unexplored.…”
mentioning
confidence: 99%
“…This approach has been applied in a small number of stress and disease studies conducted on endangered species in challenging field conditions (Aguirre et al 1995;Chapman et al 2006). For example, plasma corticosterone positively correlated with fibropapilloma virus, an emerging disease threatening endangered green turtle (Chelonia mydas; Aguirre et al 1995).…”
Section: Approaches To Understand the Relationship Between Stress Andmentioning
confidence: 99%
“…To examine the possible role of stress in determining red colobus population numbers, Chapman et al quantified patterns of faecal glucocorticoid excretion in relation to food availability [74,75]. Poor nutrition and parasite infection were expected to lead to elevated glucocorticoid levels, and a time lag was expected before this became apparent.…”
Section: (E) Glucocorticoidsmentioning
confidence: 99%
“…Methods for sample processing and analyses can be found elsewhere [74,75,80]. Glucocorticoid levels from the two groups in Kibale were contrasted to levels from red colobus inhabiting eight nearby forest fragments [74].…”
Section: (E) Glucocorticoidsmentioning
confidence: 99%